Conversations with Human Books: Promoting Respectful Dialogue, Diversity, and Empathy among Grade and High School Students. Issue 3 (2nd July 2020) - Schijf, Candy May N.; Olivar, Julieta F.; Bundalian, Jorge B.; Ramos-Eclevia, Marian
ABSTRACT: The De La Salle University (DLSU) Libraries organised the first Human Library in the Philippines in August 2014. The initial target audience were undergraduate and graduate students of the University. In 2016, the Integrated School Libraries organised Human Library sessions for grade school, junior high school, and senior high school students. The activity allowed them to engage with human books actively, facilitating an innovative learning experience. This paper describes the Human Library program of the DLSU Integrated School Libraries. The program aims to promote respectful dialogue between human books and students, foster the culture of diversity and difference, and reduce prejudice and discrimination against people with different social and cultural backgrounds. The program has been integrated with the school curriculum, thus allowing students to have the opportunity to dialogue with human books from different backgrounds, such as people with a tattoo, members of LGBTQ community, people with mental health issues, people with bipolar disorder, and people with eating disorders among others. Through this learning experience, students are expected to appreciate diversity and are more open-minded at an early age, be more accepting and kinder to others, empathetic, and respectful.